To tweet or not to tweet: the effects of social media endorsements on unfamiliar sport brands and athlete endorsers. Issue 3 (2nd July 2016) - Brison, Natasha T.; Byon, Kevin K.; Baker III, Thomas A.
Abstract : Unfamiliar sport brands are consistently searching for ways to gain the interest of consumers and to differentiate the brand's messages from the huge amount of advertising communications consumers receive on a daily basis. One of the most powerful methods used to distinguish one brand from others is an alliance with athlete endorsers. Companies are actively courting athlete endorsers and their social media accounts to reach consumers. However, little is known about the effects of these alliances. Therefore, two studies were conducted: (1) to explore the effectiveness of Twitter endorsement campaigns for unfamiliar sport brands, and (2) to investigate the influence that Twitter endorsements for unfamiliar sport brands have on athlete endorsers. The study revealed that attitude toward the unfamiliar sport brand was positively influenced by the athlete endorser's Twitter message and that trustworthiness was the dominant characteristic influencing credibility of an endorser through Twitter.